GaN LED on Quartz Substrate through Wafer Bonding and Layer Transfer Processes. (20th July 2018) - Lee, Kwang Hong; Wang, Yue; Zhang, Li; Chua, Soo Jin; Fitzgerald, Eugene A.; Tan, Chuan Seng
Abstract : A method to transfer GaN LED layers (which were grown initially on a Si substrate) to a quartz substrate is proposed and demonstrated. Quartz substrate is chosen due to its optical transparency to enhance the light extraction efficiency. The GaN LED-on-Si substrate was temporarily supported on a Si handle wafer. A quartz substrate was then bonded to the GaN LED layers-containing handle wafer. Finally, the handle wafer was released to realize the GaN LED layers on the quartz substrate. All substrates used were 200 mm in diameter. The transferred film demonstrates excellent optical properties. The GaN LED devices were then fabricated on coupon size samples using standard photolithography techniques and dry etching processes. Through this method, we can improve the light extraction efficiency and hence, benefitial to the integration of Si-CMOS + LED platform for applications such as multi-color microdisplay.